The Cambridge companion to European modernism - Lewis, Pericles Ed (Cambridge companions to topics, 2011)
"Modernism arose in a period of accelerating globalization in the late nineteenth century. Modernist writers and artists, while often loyal to their country in times of war, aimed to rise above the national and ideological conflicts of the early twentieth century in service to a cosmopolitan ideal. This Companion explores the international aspects of literary modernism by mapping the history of the movement across Europe and within each country. The essays place the various literary traditions within a social and historical context and set out recent critical debates. Particular attention is given to the urban centers in which modernism developed - from Dublin to Zürich, Barcelona to Warsaw - and to the movements of modernists across national borders. A broad, accessible account of European modernism, this Companion explores what this cosmopolitan movement can teach us about life as a citizen of Europe and of the world"--